Task shifting: A key strategy in the multipronged approach to reduce maternal mortality in India. (October 2015) - Bhushan, Himanshu; Bhardwaj, Ajey
Abstract: Task shifting from specialist to nonspecialist doctors (NSDs) is an important strategy that has been implemented in India to overcome the critical shortage of healthcare workers by using the human resources available to serve the vast population, particularly in rural areas. A competency-based training program in comprehensive emergency obstetric care was implemented to train and certify NSDs. Trained NSDs were able to provide key services in maternal health, which contribute toward reductions in maternal morbidity and mortality. The present article provides an overview of the maternal health challenges, shares important steps in program implementation, and shows how challenges can be overcome. The lessons learned from this experience contribute to understanding how task shifting can be used to address large-scale public health issues in low-resource countries and in particular solutions to address maternal health issues.